Factors to improve the interobserver agreement for gastric atrophy and intestinal metaplasia: consensus of definition and criteria. Issue 5 (19th January 2018) - Kim, Sung Sun; Kook, Myeong‐Cherl; Shin, Ok‐ran; Kim, Hee Sung; Bae, Han‐Ik; Seo, An Na; Park, Do Youn; Choi, Il Ju; Kim, Young‐Il; Nam, Byung Ho; Kim, Sohee
Abstract : Aims: Intestinal metaplasia and atrophy of the gastric mucosa are associated with Helicobacter pylori infection and are considered premalignant lesions. The updated Sydney system is used for these parameters, but experienced pathologists and consensus processes are required for interobserver agreement. We sought to determine the influence of the consensus process on the assessment of intestinal metaplasia and atrophy. Methods and results: Two study sets were used: consensus and validation. The consensus set was circulated and five gastrointestinal pathologists evaluated them independently using the updated Sydney system. The consensus of the definitions was then determined at the first consensus meeting. The same set was recirculated to determine the effect of the consensus. The second consensus meeting was held to standardise the grading criteria and the validation set was circulated to determine the influence. Two additional circulations were performed to assess the maintainance of consensus and intraobserver variability. Interobserver agreement of intestinal metaplasia and atrophy was improved through the consensus process (intestinal metaplasia: baseline κ = 0.52 versus final κ = 0.68, P  = 0.006; atrophy: baseline κ = 0.19 versus final κ = 0.43, P  < 0.001). Higher interobserver agreement in atrophy was observed after consensus regarding the definition (pre‐consensus: κ = 0.19 versus post‐consensus: κ = 0.34, P  = 0.001). There was improved interobserver agreement in intestinal metaplasia after standardisation of the grading criteria (pre‐standardisation: κ = 0.56 versus post‐standardisation: κ = 0.71, P  = 0.010). Conclusions: This study suggests that interobserver variability regarding intestinal metaplasia and atrophy may result from lack of a precise definition and fine criteria, and can be reduced by consensus of definition and standardisation of grading criteria.